PARADIGMA MATERIALISME DIALEKTIS DI ERA MILENIAL - I Wayan Kariarta (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2020)
Life in this Age provides various kinds of convenience in achieving the expected goals. There are various kinds of opportunities, possibilities and hopes that have so far not been possible now show their existence. The rapid pace of development of technology and information is one of the characteristics of the millennial era. In millennial era, we will easily find people who are multitasking. Sociable in association and able to put the difference in proportion. The existence of material in the form of money really plays a vital role in life. The material and its exchange become fine dining day-to-day, and every activity that is pursued leads to the material to be achieved Materialism is defined as a philosophical school that considers that it exists or real is just matter. Basically everything consists of matter and all phenomena is the result of material interaction. It is undeniable that understanding materialism has major contribution to the development of science. Materialism holds on a fact that is easily understood, observed and ignores abstract propositions. The term dialectics comes from the Greek word